Marshall lessons in leadership - Jeffers, H. Paul (Great generals series, 2010)
Called 'the organizer of victory' by Winston Churchill, General George C. Marshall was a skillful and compassionate leader with a unique legacy. This exciting overview of Marshall's career and his skilled combination of military strategy and politics will be an important guide for military and civilian leaders everywhere.